The effects of the Massachusetts health reform on financial distress - Bhashkar Mazumder; Sarah Miller (Federal Reserve Bank of Chicago, 2014)
A major benefit of health insurance coverage is that it protects the insured from unexpected medical costs that may devastate their personal finances. In this paper, we use detailed credit report information on a large panel of individuals to examine the effect of a major health care reform in Massachusetts in 2006 on a broad set of financial outcomes. The Massachusetts model served as the basis for the Affordable Care Act and allows us to examine the effect of coverage on financial outcomes for the entire population of the uninsured, not just those with very low incomes. We exploit plausibly exogenous variation in the impact of the reform across counties and age groups using levels of pre-reform insurance coverage as a measure of the potential effect of the reform. We find that the reform reduced the total amount of debt that was past due, the fraction of all debt that was past due, improved credit scores and reduced personal bankruptcies. We also find suggestive evidence that the reform lowered the total amount of debt and decreased third party collections. The effects are most pronounced for individuals who had limited access to credit markets before the reform. These results show that health care reform has implications that extend well beyond the health and health care utilization of those who gain insurance coverage.
Keywords: H75; I11; I13; 330; Health care reform; health insurance; financial distress